Speed and accuracy of mobile BlackBerry Messenger to transmit chest radiography images from a small community emergency department to a geographically remote referral center. (June 2016) - Scheuermeyer, Frank; Grunau, Brian; Cheyne, Jay; Grafstein, Eric; Christenson, Jim; Ho, Kendall
Background: Small emergency departments (EDs) may rely on radiologists at remote centers for interpretations of chest radiographs (CXRs). We investigated systematic transmission of CXR images from a small ED to a geographically remote referral center using the mobile BlackBerry Messenger (BBM) application. Methods: Investigators obtained de-identified CXR images of consecutive ED patients via mobile phone camera. Each CXR image, along with a brief clinical history, was sent via BBM to an emergency physician located at a remote referral site, and the receiving physician replied via BBM to confirm reception. All communications, image generation, and image analysis was conducted on mobile phones. The primary outcome was the proportion of BBMs received within two minutes of sending; the secondary outcome was the proportion of BBM replies to the sending physician within five minutes. Image accuracy—comparing the radiologist's interpretation with the receiving emergency physician's interpretation—was estimated using predefined criteria. Results: Of 1281 consecutive ED patients, 231 (18.0 %) had CXRs obtained, 320 CXRs were analyzed and 611 BBMs sent. All BBMs (100.0%, 95% confidence interval (CI) 99.4–00.0) arrived within two minutes; 595 BBMs (97.4%, 95% CI 95.8–98.4) were replied to within five minutes. Of the 58 CXRs with abnormalities requiring intervention, there were 55 concordances (overall agreement 94.2%, 95% CI 85.9–98.3; kappa 0.95, 95% CI 0.89–1.0) Conclusion: Systematic transmission of CXR images from a small ED to a remote large center using mobile phones may be a safe and effective strategy to rapidly communicate important patient information.